Sulfone polymer with narrow molecular weight distribution and low gel content and preparation method thereof
The problem of gel structure formation was solved by solvent purification and deoxygenation treatment when preparing sulfone polymers in the solution method, and a sulfone polymer material with narrow molecular weight distribution and good processing performance was obtained.
Patent Information
- Application Number
- CN202411913587.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, when preparing sulfone polymers in solution method, it is difficult to effectively remove trace oxygen in non-protic polar solvents, resulting in polymer chain branching or crosslinking, forming a gel structure, which in turn affects the molecular weight distribution and processing performance of the material.
By purifying and deoxygenating the aprotic polar solvent, the oxygen content in the reaction system is reduced, and a phased heating reaction is adopted to reduce the formation of polymer radicals, thereby controlling the gel structure content and obtaining a sulfone polymer with a narrow molecular weight distribution.
The linear structure and narrow molecular weight distribution of sulfone polymer are realized, the processing and forming performance of the material is improved, the content of the gel structure is reduced, and the use value of the product is enhanced.
Smart Images

Figure BDA0005206329610000021 
Figure BDA0005206329610000031 
Figure FDA0005206329600000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sulfone polymer materials, and in particular relates to a sulfone polymer with narrow molecular weight distribution and low gel content and a preparation method thereof. Background Art
[0002] Sulfone polymer is an important thermoplastic special engineering plastic, mainly including polyethersulfone (PES), bisphenol A polysulfone (PSU), polyphenylene sulfone (PPSU), etc. Sulfone polymer resin has excellent properties, such as excellent mechanical properties, high temperature resistance, chemical corrosion resistance, aging resistance, etc. These characteristics make this type of resin material widely used in many fields such as aerospace, national defense, electronics and electrical, medical, nuclear power, oil wells, ships, magnetic wires, military industry, automobile manufacturing industry and food processing.
[0003] Sulfone polymers are generally prepared by solution method, and the solvents used are usually non-protonic polar solvents. However, this type of solvent has a strong polarity and is very easy to combine with oxygen. The trace oxygen present in the non-protonic polar solvent used in the solution method for preparing sulfone polymers is difficult to remove. In the subsequent polymerization reaction, under high temperature conditions, this part of the combined oxygen will attack the CH bonds on the polymer chain to form active polymer free radicals, which will continue to attack the polymer chain to form a branched or cross-linked structure (i.e., gel structure). The formation of this gel structure will cause the molecular weight distribution of sulfone polymer materials to become wider, reduce its solubility, and increase melt viscosity, which will not only affect the processing and molding performance in downstream applications, but also cause pitting (crystal points) on the surface of transparent thin-walled parts, seriously reducing the use value of the product.
[0004] In view of this, it is necessary to further study and improve the process operation of preparing sulfone polymers by solution method to obtain sulfone polymer resins with narrow molecular weight distribution and low gel content. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems existing in the preparation of sulfone polymers by a solution method, and to provide a sulfone polymer with a narrow molecular weight distribution and a low gel content and a preparation method thereof; the present invention has clarified the mechanism and influencing factors of the generation of gel structure in sulfone polymers through exploration, and by removing the bound oxygen in the non-protonic polar solvent used and deoxygenating the reaction system, the oxygen content in the reaction system is reduced, and the generation of polymer free radicals is reduced, thereby controlling the gel structure content and obtaining a linear sulfone polymer material with a narrow molecular weight distribution.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, a sulfone polymer having a narrow molecular weight distribution and low gel content is provided, having the following properties:
[0008] Molecular weight distribution <3 (e.g., 0.1, 0.5, 1, 1.5, 1.8, 2, 2.2, 2.5, 2.8);
[0009] The gel structure content is greater than 0 and less than 3 mol% (for example, infinitely close to 0, 0.01 mol%, 0.02 mol%, 0.05 mol%, 0.1 mol%, 0.2 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 2.8 mol%, 2.9 mol%);
[0010] The general structural formula of the sulfone polymer is shown in Formula 1,
[0011]
[0012] In Formula 1, X is a biphenyl group, an isopropylidene group or a sulfone group; and n is in the range of 5 to 100 (e.g., 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 50, 60, 70, 80, 90, 95, 98).
[0013] In the text, the gel structure can be understood as one or more of the cross-linked and branched structures formed by the continued polymerization or grafting of the sulfone polymer shown in Formula 1.
[0014] The gel structure has a variety of structural forms, and the simplest structure is shown in Formula 2:
[0015]
[0016] In formula 2, X is biphenyl, isopropylidene or sulfone; and the value of n is in the range of 5-100.
[0017] The sulfone polymer has four sites that are easily attacked by free radicals (sites a1, a2, b1, and b2 in the structure shown in Formula 1), and under certain conditions, a variety of branched and cross-linked structures including the structure shown in Formula 2 will be generated.
[0018] In a second aspect, a method for preparing the sulfone polymer as described above is provided, comprising the steps of:
[0019] 1) adding an organic bisphenol compound, 4,4'-dichlorodiphenyl sulfone, a salt-forming agent and a purified aprotic polar solvent into a reactor, stirring and mixing the system to uniformly perform a deoxygenation operation, and controlling the oxygen content in the system to be less than or equal to 100 ppm (for example, 0.1 ppm, 0.5 ppm, 1 ppm, 2 ppm, 4 ppm, 5 ppm, 10 ppm, 15 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 95 ppm);
[0020] 2) After the replacement is completed, an inert gas (such as nitrogen) is continuously passed through the system, and a two-stage temperature increase reaction is carried out under this condition to obtain a viscous sulfone polymer solution.
[0021] According to the preparation method provided by the present invention, in some embodiments, the organic bisphenol compound is selected from one or more of bisphenol A, bisphenol F, dihydroxydiphenyl sulfone, hydroquinone, resorcinol, dihydroxybenzophenone, dihydroxydiphenyl ether, 4,4'-biphenol, hexafluorobisphenol A, tetrabromobisphenol A and dihydroxynaphthalene.
[0022] In some embodiments, the salt-forming agent is selected from one or more of potassium carbonate, sodium carbonate, sodium hydroxide and potassium hydroxide.
[0023] In some embodiments, the aprotic polar solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, sulfolane, diphenyl sulfone, dimethyl sulfone and biphenylphenylsulfenyl.
[0024] According to the preparation method provided by the present invention, in some embodiments, the operation of purifying the aprotic polar solvent is: at room temperature, an inert gas (such as nitrogen) is bubbled into the aprotic polar solvent for purification treatment for 1 to 10 hours (for example, 1.5 hours, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 9 hours).
[0025] According to the preparation method provided by the present invention, in some embodiments, in step 1), the molar ratio of the organic bisphenol compound to 4,4'-dichlorodiphenyl sulfone is 1:0.95 to 1:1.05 (for example, 1:0.96, 1:0.98, 1:0.99, 1:1, 1:1.01, 1:1.02, 1:1.04), preferably 1:0.97 to 1:1.03.
[0026] In some embodiments, in step 1), the molar ratio of the organic bisphenol compound to the salt-forming agent is 1:1 to 1:1.5 (e.g., 1:1.05, 1:1.2, 1:1.25, 1:1.35, 1:1.4), preferably 1:1.1 to 1:1.3.
[0027] In some embodiments, in step 1), the molar ratio of the organic bisphenol compound to the aprotic polar solvent is 1:5 to 1:30 (e.g., 1:6, 1:8, 1:10, 1:15, 1:18, 1:22, 1:25, 1:28), preferably 1:10 to 1:20.
[0028] In some embodiments, in step 1), the operation of deoxygenating the system is: performing vacuum-nitrogen replacement, and the number of replacements is 3 to 10 times (for example, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times).
[0029] According to the preparation method provided by the present invention, in some embodiments, in step 2), the flow rate of the long-flow inert gas (such as nitrogen) is 0.1L / min to 1L / min, for example, 0.15L / min, 0.2L / min, 0.25L / min, 0.3L / min, 0.4L / min, 0.5L / min, 0.6L / min, 0.7L / min, 0.8L / min, 0.9L / min, 0.95L / min; the flow rate range is based on a 10L reactor (if the reactor volume changes, the flow rate range is changed according to the ratio of the reactor size; for example, the reactor size is 1L, and the long-flow inert gas flow rate is 0.01L / min to 0.1L / min).
[0030] In the present invention, the inert gas flow rate is controlled within a certain range, which is conducive to removing dissolved oxygen in the system, thereby reducing or even avoiding the generation of polymer free radicals. In conventional operations in the art, when deoxygenating the system gas by replacing the inert gas, most of the removed oxygen is free oxygen, and dissolved oxygen is not easy to be effectively removed.
[0031] In some embodiments, in step 2), the process conditions of the first stage temperature increase reaction include: the reaction temperature is 100-140°C (for example, 105°C, 110°C, 120°C, 130°C, 135°C), and the reaction time is 2-10h (for example, 3h, 4h, 5h, 6h, 8h, 9h); the process conditions of the second stage temperature increase reaction include: the reaction temperature is 140-220°C (for example, 145°C, 150°C, 160°C, 180°C, 200°C, 210°C), and the reaction time is 2-10h (for example, 3h, 4h, 5h, 6h, 8h, 9h).
[0032] In the present invention, the time of the system in the high temperature stage is reduced by staged reaction, which is beneficial to reduce the generation of cross-linking or branched structures.
[0033] The beneficial effects of the technical solution of the present invention are at least:
[0034] The present invention reduces the oxygen content (free oxygen and bound oxygen) in the reaction system and the generation of polymer free radicals, thereby controlling the gel structure content. The invention also adopts a staged reaction to reduce the time of the system in the high temperature stage, which is beneficial to further reduce the generation of cross-linked or branched structures, and can obtain a linear sulfone polymer material with a narrow molecular weight distribution. In addition, the processing and molding performance of the obtained sulfone polymer material in downstream applications can be improved, thereby enhancing the use value of the sulfone polymer material product. DETAILED DESCRIPTION
[0035] In order to understand the technical features and content of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. For those who do not specify specific conditions in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer.
[0036] The source information of the main raw materials in each embodiment is as follows:
[0037] Bisphenol A, Wanhua Chemical;
[0038] 4,4'-Dichlorodiphenyl sulfone, Hebei Xulong Chemical Co., Ltd.;
[0039] N,N-Dimethylacetamide, Jiutian Chemical Co., Ltd.
[0040] Sulfolane, Liaoyang Yanghua Chemical Co., Ltd.;
[0041] N-Methylpyrrolidone, Wanhua Chemical.
[0042] Embodiment 1:
[0043] A 1L four-necked flask with a water separator, a condenser and a mechanical stirrer was placed in an oil bath, and 0.25 mol of bisphenol A, 0.375 mol of potassium carbonate, 0.25 mol of 4,4'-dichlorodiphenyl sulfone, and 1.25 mol of purified N,N-dimethylacetamide (purified by passing nitrogen through N,N-dimethylacetamide for 1 h) were added to the four-necked flask in sequence, and stirring was started to mix the materials evenly, and then the system was vacuum-nitrogen replaced 3 times, and the oxygen content in the system was 100 ppm;
[0044] After the replacement is completed, nitrogen is continuously passed through the system at a nitrogen flow rate of 0.01 L / min; and a two-stage temperature increase reaction is carried out under this atmosphere, namely: the system reaction temperature is increased to 140°C, and the reaction is stirred for 2 hours, and then the system reaction temperature is continued to be increased to 160°C, and the reaction is carried out for 10 hours to obtain a viscous sulfone polymer solution.
[0045] Embodiment 2:
[0046] Place a 1L four-necked flask with a water separator, a condenser and a mechanical stirrer in an oil bath, add 1 mol of 4,4'-biphenol, 1 mol of potassium carbonate, 1.05 mol of 4,4'-dichlorodiphenyl sulfone, and 30 mol of purified N,N-dimethylacetamide (purified by passing nitrogen through N,N-dimethylacetamide for 10 hours) into the four-necked flask in sequence, start stirring to mix the materials evenly, and then perform vacuum-nitrogen replacement on the system 10 times, and the oxygen content in the system is 1 ppm;
[0047] After the replacement was completed, nitrogen was continuously passed through the system at a nitrogen flow rate of 0.1 L / min; and a two-stage temperature increase reaction was carried out under this atmosphere, namely: the system reaction temperature was increased to 100°C, and the reaction was stirred for 10 hours, and then the system reaction temperature was continued to be increased to 140°C, and the reaction was carried out for 10 hours to obtain a viscous sulfone polymer solution.
[0048] Embodiment 3:
[0049] In a 10L reactor equipped with a water separator, a condenser, a heater and a mechanical stirrer, 5 mol of bisphenol A, 6 mol of sodium carbonate, 4.75 mol of 4,4'-dichlorodiphenyl sulfone, and 75 mol of purified sulfolane (purified by passing nitrogen through sulfolane for 5 hours) were added in sequence, stirring was started to mix the materials evenly, and then the system was vacuum-nitrogen replaced 5 times, and the oxygen content in the system was 40 ppm;
[0050] After the replacement is completed, nitrogen is continuously passed through the system at a nitrogen flow rate of 0.5 L / min; and a two-stage temperature increase reaction is carried out under this atmosphere, namely: the system reaction temperature is increased to 130°C, and the reaction is stirred for 5 hours, and then the system reaction temperature is continued to be increased to 220°C, and the reaction is carried out for 2 hours to obtain a viscous sulfone polymer solution.
[0051] Embodiment 4:
[0052] A 1L four-necked flask with a water separator, a condenser and a mechanical stirrer was placed in an oil bath, and 0.25 mol of bisphenol S, 0.3 mol of potassium carbonate, 0.25 mol of 4,4'-dichlorodiphenyl sulfone, and 3.75 mol of purified N-methylpyrrolidone (purified by passing nitrogen in N-methylpyrrolidone for 10 h) were added to the four-necked flask in sequence, and stirring was started to mix the materials evenly, and then the system was vacuum-nitrogen replaced 10 times, and the oxygen content in the system was 1 ppm;
[0053] After the replacement is completed, nitrogen is continuously passed through the system at a nitrogen flow rate of 0.1 L / min; and a two-stage temperature increase reaction is carried out under this atmosphere, namely: the system reaction temperature is increased to 140°C, and the reaction is stirred for 10 hours, and then the system reaction temperature is continued to be increased to 200°C, and the reaction is carried out for 5 hours to obtain a viscous sulfone polymer solution.
[0054] Comparative Example 1:
[0055] A 1L four-necked flask with a water separator, a condenser and a mechanical stirrer was placed in an oil bath, 0.25 mol of bisphenol S, 0.3 mol of potassium carbonate, 0.25 mol of 4,4'-dichlorodiphenyl sulfone, and 3.75 mol of unpurified N-methylpyrrolidone were added to the four-necked flask in sequence, stirring was started to mix the materials evenly, and then the system was vacuum-nitrogen replaced 3 times, and the oxygen content in the system was 200 ppm;
[0056] After the replacement was completed, nitrogen was continuously passed through the system at a nitrogen flow rate of 0.01 L / min; and the temperature was raised to react under this atmosphere, that is, the reaction temperature of the system was raised to 200° C. and reacted for 10 hours to obtain a viscous sulfone polymer solution.
[0057] Comparative Example 2:
[0058] A 1L four-necked flask with a water separator, a condenser and a mechanical stirrer was placed in an oil bath, and 0.25 mol of bisphenol A, 0.3 mol of potassium carbonate, 0.25 mol of 4,4'-dichlorodiphenyl sulfone, and 3.75 mol of purified N-methylpyrrolidone (purified by passing nitrogen gas through N-methylpyrrolidone for 10 h) were added to the four-necked flask in sequence, and stirring was started to mix the materials evenly. The gas in the vacuum-nitrogen replacement system was not set to deoxygenate, and the oxygen content in the system was 320 ppm;
[0059] After the replacement was completed, nitrogen was continuously passed through the system at a nitrogen flow rate of 0.1 L / min; and the temperature was raised under this atmosphere, that is, the reaction temperature of the system was raised to 200° C. and the reaction was carried out for 10 hours to obtain a viscous sulfone polymer solution.
[0060] Comparative Example 3:
[0061] A 1L four-necked flask with a water separator, a condenser and a mechanical stirrer was placed in an oil bath, 0.25 mol of bisphenol S, 0.3 mol of potassium carbonate, 0.25 mol of 4,4'-dichlorodiphenyl sulfone, and 3.75 mol of unpurified N-methylpyrrolidone were added to the four-necked flask in sequence, stirring was started to mix the materials evenly, and then the system was vacuum-nitrogen replaced 10 times, and the oxygen content in the system was 150 ppm;
[0062] After the replacement is completed, nitrogen is continuously passed through the system at a nitrogen flow rate of 0.1 L / min; and a two-stage temperature increase reaction is carried out under this atmosphere, namely: the system reaction temperature is increased to 140°C, and the reaction is stirred for 10 hours, and then the system reaction temperature is continued to be increased to 200°C, and the reaction is carried out for 5 hours to obtain a viscous sulfone polymer solution.
[0063] The performance indicators of the sulfone polymers obtained in each embodiment and comparative example were tested, and the testing method was as follows:
[0064] 1) Weight average molecular weight Mw and its molecular weight distribution: gel permeation chromatography (GPC);
[0065] 2) Gel structure content: gel permeation chromatography (GPC).
[0066] The test results are shown in Table 1 below.
[0067] Table 1 Performance test results of sulfone polymers
[0068] serial number <![CDATA[Mw / 10 4 ]]> Molecular weight distribution Gel structure content / mol% Example 1 7.56 2.68 2.35 Example 2 6.92 1.73 0.54 Example 3 9.39 2.05 1.27 Example 4 8.57 1.27 0.11 Comparative Example 1 7.43 3.85 7.32 Comparative Example 2 6.22 4.31 8.17 Comparative Example 3 7.91 2.59 6.64
[0069] The sulfone polymer resins obtained in the examples and comparative examples were processed and molded. The specific operation steps were as follows: an injection molding machine was used to injection mold the obtained sulfone polymer resin into a sample with a thickness of 2 mm and a length and width of 6 cm respectively.
[0070] Then the processed sample parts are tested for processing fluidity, optical properties, and crystal point content. The test method is as follows:
[0071] Processing fluidity test: The melt index is measured using a melt index tester under the conditions of 365°C and 5kg;
[0072] Optical performance test: using Lab tester;
[0073] Crystal point content test: use fisheye instrument.
[0074] The test results are shown in Table 2.
[0075] Table 2 Performance test results of molded parts
[0076] serial number Optical properties (yellowness) <![CDATA[Crystal point content (pcs / cm 2 )]]> Melt index Example 1 14 20 20 Example 2 8 4 33 Example 3 10 13 25 Example 4 6 2 36 Comparative Example 1 48 402 12 Comparative Example 2 53 557 8 Comparative Example 3 45 389 15
[0077] It can be seen from the results in Table 1 and Table 2 that the technical solution of this patent is adopted to control the content of free oxygen and bound oxygen in the non-protonic polar solvent and the reaction system, which can effectively reduce the generation of polymer free radicals, and the staged reaction is adopted to reduce the time of the system in the high temperature stage, which is conducive to further reducing the generation of cross-linking or branching structures, so that the prepared sulfone polymer has a low gel content and a narrow molecular weight distribution. The sulfone polymer resin is processed into a product, which has good processing and molding properties, a small content of crystal points on the surface of the product, and excellent optical properties.
[0078] Compared with the embodiments, in Comparative Example 1, the solvent was not purified and the reaction was performed in a one-step process, resulting in a high gel content and a wide molecular weight distribution of the obtained product, the processing fluidity and optical properties of the parts made from the resin were reduced, and the crystal point content was high; in Comparative Example 2, no vacuum-nitrogen replacement operation was set and the reaction was performed in a one-step process, resulting in a high gel content and a wide molecular weight distribution of the obtained product, the processing fluidity and optical properties of the parts made from the resin were reduced, and the crystal point content was high; in Comparative Example 3, the solvent was not purified, resulting in a high gel content and a wide molecular weight distribution of the obtained product, the processing fluidity and optical properties of the parts made from the resin were reduced, and the crystal point content was high.
[0079] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.
Claims
1. A sulfone polymer having a narrow molecular weight distribution and a low gel content, characterized in that: It has the following properties: Molecular weight distribution <3; The gel structure content is greater than 0 and less than 3 mol%; The general structural formula of the sulfone polymer is shown in Formula 1, In formula 1, X is biphenyl, isopropylidene or sulfone; and n is in the range of 5-100.
2. The method for preparing a sulfone polymer according to claim 1, characterized in that: The steps include: 1) adding an organic bisphenol compound, 4,4'-dichlorodiphenyl sulfone, a salt-forming agent and a purified aprotic polar solvent into a reactor, stirring and mixing the system uniformly, and then performing a deoxygenation operation to control the oxygen content in the system to be less than or equal to 100 ppm; 2) After the replacement is completed, an inert gas is passed through the system for a long time, and a two-stage temperature increase reaction is carried out under this condition to obtain a viscous sulfone polymer solution.
3. The preparation method according to claim 2, characterized in that: The organic bisphenol compound is selected from one or more of bisphenol A, bisphenol F, dihydroxydiphenyl sulfone, hydroquinone, resorcinol, dihydroxybenzophenone, dihydroxydiphenyl ether, 4,4'-biphenol, hexafluorobisphenol A, tetrabromobisphenol A and dihydroxynaphthalene.
4. The preparation method according to claim 2 or 3, characterized in that: The salt-forming agent is selected from one or more of potassium carbonate, sodium carbonate, sodium hydroxide and potassium hydroxide.
5. The preparation method according to any one of claims 2 to 4, characterized in that: The aprotic polar solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, sulfolane, diphenyl sulfone, dimethyl sulfone and biphenylphenylsulfenyl.
6. The preparation method according to any one of claims 2 to 5, characterized in that: The operation of purifying the aprotic polar solvent is as follows: at room temperature, an inert gas is blown into the aprotic polar solvent for purification for 1 to 10 hours.
7. The preparation method according to any one of claims 2 to 6, characterized in that: In step 1), the molar ratio of the organic bisphenol compound to 4,4'-dichlorodiphenyl sulfone is 1:0.95 to 1:1.05, preferably 1:0.97 to 1:1.03; In step 1), the molar ratio of the organic bisphenol compound to the salt-forming agent is 1:1 to 1:1.5, preferably 1:1.1 to 1:1.3; In step 1), the molar ratio of the organic bisphenol compound to the aprotic polar solvent is 1:5 to 1:30, preferably 1:10 to 1:
20.
8. The preparation method according to any one of claims 2 to 7, characterized in that: In step 1), the operation of deoxygenating the system is: vacuum-nitrogen replacement, the replacement times are 3 to 10 times.
9. The preparation method according to any one of claims 2 to 8, characterized in that: In step 2), the flow rate of the long-flow inert gas is 0.1 L / min to 1 L / min; the flow rate range is based on a 10 L reactor.
10. The preparation method according to any one of claims 2 to 9, characterized in that: In step 2), the process conditions of the first stage temperature reaction include: reaction temperature of 100-140°C, reaction time of 2-10h; the process conditions of the second stage temperature reaction include: reaction temperature of 140-220°C, reaction time of 2-10h.
Citation Information
Patent Citations
Industrialized synthesis method of cladodification high-strength polysulfone resin
CN105348513A
Method for preparing polysulfone resin material by adopting synergistic dehydration process
CN111662453A
Polyether sulfone and preparation method thereof
CN113278150A
Method for improving conductivity of polysulfone polymer
CN115322376A
Method for synthesizing polyethersulfone resin
CN116120556A
Cited By
Sulfone polymer and preparation method thereof
CN120966008A
Sulfone polymers and methods for making the same
CN120966008B